Relevansi Konsep Pendidikan Akhlak dalam Kitab Ayyuhal Walad dan Serat Wulangreh dengan Pendidikan Saat Ini - Tri Agus Santoso; Usman Abu Bakar; A. Dardiri Hasyim (Departement of Mathematics Education, 2023)
Moral education is the most important part of human life. This study aims to analyze and compare the concept of moral education in the book Ayyuhal Walad by Imam Ghazali and Serat Wulangreh by Paku Buwono IV. This type of research is library research (Library Research). The approach used in this study is a descriptive historical approach. The results of this study are in the Book of Ayyuhal Walad by Imam Ghazali and Serat Wulangreh by Paku Buwono IV, that: a) the sources of moral education are the Koran, al-sunah, ijmak, qiyas, b) The purpose of education morals, namely that knowledge is put into practice, has a good personality and stays away from bad behavior, seeking knowledge with the aim of seeking a formal diploma is inappropriate and inappropriate because it is part of the goals of the world, c) Educational material, namely material for spiritual and inner (heart) education originating from the Shari'a which includes monotheism, tasawuf, ubudiyah and dhauq, which dhauq cannot be achieved except by practicing it, d) Everyone who studies knowledge must have a teacher or murshid. A teacher or student must have good behavior or morals, have good knowledge, riyadhoh and mujahadah. Methods of moral education, namely the method of storytelling.